2011
DOI: 10.1254/jphs.11065fp
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Efonidipine on TGF-β1–Induced Cardiac Fibrosis Through Smad2-Dependent Pathway in Rat Cardiac Fibroblasts

Abstract: Transforming growth factor beta-1 (TGF-β1) plays a critical role in progression of cardiac fibrosis, which may involve intracellular calcium change. We examined effects of efonidipine, a dual T-type and L-type calcium channel blocker (CCB), on TGF-β1–induced fibrotic changes in neonatal rat cardiac fibroblast. T-type and L-type calcium channel mRNAs were highly expressed in cultured cardiac fibroblasts. TGF-β1 (5 ng/mL) significantly increased Smad2 phosphorylation and [3H]-leucine incorporation, which were at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…⁄ P < 0.05 vs. NC + Ang II. modulation of calcium channels and calcium related proteins have been reported to be beneficial to anti-fibrosis [39,40]. Experimental and clinical data have demonstrated that Mg 2+ deficiency can elicit the elevation of intracellular Ca 2+ concentrations, formation of oxygen radicals and pro-inflammatory agents and changes in membrane permeability as well as transport processes in cardiac cells [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…⁄ P < 0.05 vs. NC + Ang II. modulation of calcium channels and calcium related proteins have been reported to be beneficial to anti-fibrosis [39,40]. Experimental and clinical data have demonstrated that Mg 2+ deficiency can elicit the elevation of intracellular Ca 2+ concentrations, formation of oxygen radicals and pro-inflammatory agents and changes in membrane permeability as well as transport processes in cardiac cells [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Transfection of cardiac fibroblasts with small interfering RNA (siRNA) was performed as previously described (20). The silencer predesigned siRNA against MMP-2 (s135546; Life Technologies, Carlsbad, CA) was synthesized according to rat-specific sequences.…”
Section: Methodsmentioning
confidence: 99%
“…-related protein has been reported have antifibrosis effects (28,29). Although the expression of some TRP channels can be detected by using RT-PCR and appears to be associated with cardiac fibrosis, many of them cannot be detected by using electrophysiological recordings (6,30).…”
Section: +mentioning
confidence: 99%